2021
DOI: 10.1186/s12885-021-07821-9
|View full text |Cite
|
Sign up to set email alerts
|

False negative rate at 18F-FDG PET/CT in para-aortic lymphnode involvement in patients with locally advanced cervical cancer: impact of PET technology

Abstract: Background The identification of factors responsible for false negative (FN) rate at 18F- Fluorodeoxyglucose (FDG) Positron Emission Tomography /Computed Tomography (PET/CT) in para-aortic (PA) lymph nodes in the presurgical staging of patients with locally advanced cervical cancer (LACC) is challenging. The aim of this study was to evaluate the impact of PET/CT technology. Methods A total of 240 consecutive patients with LACC (International Federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In order to balance increased morbidity with the benefit of surgery, selecting eligible patients for PALN dissection based on prognostic factors of PALN involvement is of significant value. Several studies have confirmed that an increased risk of PALN involvement exists in patients with pelvic lymph node metastases [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In order to balance increased morbidity with the benefit of surgery, selecting eligible patients for PALN dissection based on prognostic factors of PALN involvement is of significant value. Several studies have confirmed that an increased risk of PALN involvement exists in patients with pelvic lymph node metastases [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 92%
“…These articles were not part of the initial search result, because the title nor abstract included the 'lymphadenectomy' search term or synonyms. The final analysis included 16 studies [14,15,18,19,[25][26][27][28][29][30][31][32][33][34][35][36] reporting on 18 cohorts which were suitable for quantitative meta-analysis with pooling of upstaging outcomes.…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations